Willingness to share information via mobile application : the risk-benefit perspective - Paalimäki, Mari (2022)
Increased time spent online, and the increased use of mobile devices and applications have raised consumer privacy concerns. With advanced technology enables efficient data collection through mobile devices, thus consumers are demanding more control for information sharing. Major technology companies have announced that they will stop third-party data collection and are already offering consumers ways to block data collection. This has significant implications for the effectiveness of digital marketing, as third-party information has been used to optimize digital marketing. Therefore, companies should focus on first-party data collection to ensure that digital marketing can implement effectively in the future. This study examines mobile app users’ decision-making in information sharing from a risk-benefit perspective and test the moderating effect of technology anxiety. In addition, the study examines whether users' willingness to share information affects their acceptance of in-app messages. The study was implemented as an experimental study, where the impact of the app's data processing notifications on the privacy risk and personalization experienced by the user was tested. The respondents were randomly divided into four different groups, which were treated with a low or high level of privacy risk and a low or high level of personalization, depending on the group. After treatment, each respondent answered the same online questionnaire. A total of 400 respondents answered the survey. The results of the study confirm the importance of trust in the willingness to share information. In addition, the results suggest that personalization strengthens trust, increases the users’ willingness to share information, and increases the intention to accept in-app messages. In addition, the research results suggest that privacy risk notifications regarding data processing increased users' privacy concerns, providing a new perspective on the kind of information may reduce users' trust in the app and thus reduces the willingness to share information.